2022
DOI: 10.1111/jam.15622
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: Gut microbiota, metabolism and inflammation in hypertensive intracerebral haemorrhage

Abstract: Aims: In recent years, the incidence rate of hypertensive intracerebral haemorrhage (HICH) has been increasing, accompanied by high mortality and morbidity, which has brought a heavy burden to the social economy. However, the pathogenesis of HICH is still unclear. This study intends to explore the mechanism of gut microbiota metabolism and inflammation in the process of HICH to provide a theoretical basis for the diagnosis and treatment of HICH.Methods and Results: HE staining showed that the brain tissues of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Akkermansia muciniphila is the most important species in Verrucomicrobiota, and were more significant enrichment in ICH. Two recent studies that included 10 patients each with parenchymal hemorrhage reported a significant increase in abundance of Verrucomicrobiota (Li et al, 2022;Xiong et al, 2022), which is consistent with our results. This bacteria uses mucin O-glycan, a major component of intestinal mucus, as the main carbon source and is sialidase-rich species, while excessive degradation of mucin by microbiome can exacerbate intestinal inflammation (Patel et al, 2022;Yao et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Akkermansia muciniphila is the most important species in Verrucomicrobiota, and were more significant enrichment in ICH. Two recent studies that included 10 patients each with parenchymal hemorrhage reported a significant increase in abundance of Verrucomicrobiota (Li et al, 2022;Xiong et al, 2022), which is consistent with our results. This bacteria uses mucin O-glycan, a major component of intestinal mucus, as the main carbon source and is sialidase-rich species, while excessive degradation of mucin by microbiome can exacerbate intestinal inflammation (Patel et al, 2022;Yao et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…At the genus level, Streptococcus, Lactobacillus, Bifidobacterium, and Akkermansia were found to be abundant in ICH patients ( Chen et al, 2022 ). Moreover, Li et al (2022b) and Xiong et al (2022) reported that the abundance of Akkermansia in patients with parenchymal hemorrhage was significantly increased. Several animal model studies consistently indicated that ICH is characterized by a significant increase in Actinomycetes, Bacteroidetes, and Firmicutes, with minor changes in other bacterial populations ( Yu et al, 2021a ; Zhang et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent research, ICH has been found to be associated with alterations in the composition of the gut microbiota. Li W. et al (2022) demonstrated significant changes in the abundance of Firmicutes , Proteobacteria , and Verrucomicrobia in the gut microbiota following the occurrence of ICH, as compared to a healthy gut microbiota. At the taxonomic level of genus, a notable decrease in the abundance of Bacteroides, Blautia, Faecalibacterium, Subdoligranulum, Bifidobacterium, Agathobacter , and Romboutsia was observed, whereas a significant increase in the abundance of Escherichia-Shigella , Akkermansia , Lactobacillus , and Lachnoclostridium was evident.…”
Section: The Function Of Mgba In Ichmentioning
confidence: 94%